Comparison of Component-Resolved Diagnosis by Using Allergen Microarray With the Conventional Tests in Allergic Rhinitis Patients: The First Using in Korea - Jung, Joo Hyun; Kang, Il Gyu; Kim, Seon Tae (Clinical and experimental otorhinolaryngology, 2015)
The aim of this study was to evaluate the component-resolved diagnosis using a microarray allergen chip (Immuno Solid-phase Allergen Chip, ImmunoCAP ISAC) and to compare this new diagnostic tool with the established ImmunoCAP methods for allergen-specific IgE detection in allergic rhinitis patients. One hundred sixty-eight allergic rhinitis patients were included in this study. All the patients were diagnosed with allergic rhinitis according to their clinical symptoms, physical examination and a positive skin prick test. We analyzed their specific IgEs for house dust mites (Dermatophagoides farine [DF] and Dermatophagoides pteronyssinus [DP]), Alternaria alternata, birch, and mugwort using ImmunoCAP and ImmunoCAP ISAC in the same patient sample. We compared the sensitivity and correlation between the two tests. In cases of allergies to DP and DF, the sensitivity of the specific IgE was 80% and that of the allergen microarray was 78.9%. The correlation between the two tests was significant for both DP and DF (P<0.001). For the A. alternata, birch and mugwort allergens, the sensitivity of ImmunoCAP ISAC was slightly lower than that of ImmunoCAP. These results suggest that the allergen microarray chip method is a reliable new method to diagnose the components of an allergen in patients with allergic rhinitis sensitive to house dust mites. Further study about the utility of the allergen microarray is needed.